Perancangan Prototype Smart Lock Door Multi Sensor Berbasis Arduino Uno Menggunakan Metode VDI 2221 (Verein Deutcher Ingeniure) - Misbakhul Munir (Pusat Riset dan Inovasi Nasional, 2023)
The development of an automation system is one of the efforts for efficiency and effectiveness in the use of technology, this can be applied to apartment unit doors. A security system on the door, the process of opening or locking the door is usually done manually using a key. Smart Lock Door is a development of conventional door locks or padlocks by carrying out several additional sensor developments. This study uses Arduino Uno as a microcontroller as a selenoid brain by carrying out several programming commands. The addition of smoke sensors and fire sensors is used to make it easier for workers to a work accident occurs to get out of the work room. Smart Lock Door is an additional emergency facility in the workspace. The method used is the VDI 2221 method by approaching the product to be made by carrying out several questionnaire collection processes, with the aim that we can realize the user's wishes for the product and making it easier for users to operate the Smart lock door device. Tool testing against the VDI 2221 method is also very influential with the success rate of the Smart lock door tool.